Valproate as an adjunct to neuroleptic medication for the treatment of acute episodes of mania: A Prospective, Randomized, Double-Blind, Placebo-Controlled, Multicenter Study - Müller-Oerlinghausen, Bruno; Retzow, Angelika; Henn, Fritz A.; Giedke, Henner; Walden, Jörg (Journal of clinical psychopharmacology, 2000)
To compare the efficacy of sodium valproate administered as adjunct to neuroleptic medication for patients with acute mania with the efficacy of neuroleptics alone, the authors conducted a 21-day, randomized, double-blind, parallel-group, placebo-controlled trial. The study design closely reflected a clinical psychiatric setting in Europe where patients with acute mania commonly receive neuroleptic medication. In this trial, 136 hospitalized patients met the ICD-10 criteria for acute manic episodes; these patients received a fixed dose of 20 mg/kg of body weight of sodium valproate (Orfiril, Desitin Arzneimittel GmbH, Hamburg, Germany) orally, in addition to basic neuroleptic medication, preferably haloperidol and/or perazine. The primary outcome measure was the mean dose of neuroleptic medication (after conversion into haloperidol-equivalents) for the 21-day study period. Severity of symptoms was measured using the Young Mania Rating Scale (YMRS), the Global Assessment Scale, and the Clinical Global Impression Scale. Intent-to-treat analysis was based on 69 patients treated with valproate and 67 patients who received placebo. Groups were comparable with regard to demographic and clinical baseline data. Premature discontinuations occurred in only 13% of the patients. The mean neuroleptic dose declined continuously in the valproate group, whereas only slight variations were observed in the placebo group; the difference was statistically significant (p = 0.0007) for study weeks 2 and 3. The combination of neuroleptic and valproate proved superior to neuroleptics in attempts to alleviate manic symptoms. The proportion of responders (a 50% improvement rate shown on the YMRS) was higher for the combination with valproate than for the group receiving only neuroleptics (70% vs. 46%; p = 0.005). Adverse events consisted of those known for valproate or neuroleptics; the only adverse event was asthenia, which occurred more frequently with the combination therapy. Valproate represents a useful adjunct medication for the treatment of acute manic symptoms. Valproate is beneficial because it allows the administration of fewer neuroleptic medications and produces improved and quicker remission of manic symptoms.